Evaluation of Road Pavement Performance and Conditions Simp. Duku (Ketaping) – Pariaman Section - Yosritzal, Yosritzal; Kurniawan, Aidil; Putri, Elsa Eka (CIVED, 2023)
Road section Simp. Duku (Ketaping) - Pariaman is one of the strategic routes in the area of ​​West Sumatra Province. This road section has the potential to be developed because it is a fast lane to the Minangkabau International Airport and the City of Padang as the center of government for the Province of West Sumatra. This study aims to determine the performance of the Simp. Duku (Ketaping) – Pariaman seen from the level of service which refers to MKJI 1997 and the value of road pavement conditions at STA 16+420 to STA 20+500 refers to the PCI (Pavement Condition Index). From the research results for the Performance of Jalan Simp. Duku (Ketaping) - Pariaman is at service level D (0.91 <93) during peak hours (17-00 to 18.00 WIB). Meanwhile, from the analysis conditions of Pavement use the Pavement Condition Index (PCI) method, a PCI value of 53.69 was obtained, which means that the pavement condition was generally poor, dominated by grain ejection damage (63.23%) and crocodile skin crack damage (20.75%). ). For handling of road pavement conditions, after being correlated with the Pavement Condition Index (IKP) from the Ministry of Public Works, the type of handling is Reconstruction / Recycling.